An Internet of Things infrastructure for gait characterization in assisted living environments and its application in the discovery of associations between frailty and cognition - Iván González; Fco Javier Navarro; Jesús Fontecha; Luis Cabañero-Gómez; Ramón Hervás (International Journal of Distributed Sensor Networks)
This article presents an easy-to-deploy and low-cost Internet of Things infrastructure for gait characterization based on a set of wireless inertial sensors, called nodes, connected to the same local area network. These nodes allow acquiring inertial raw data from the trunk of each frail elder involved in explicit gait trials carried out directly in the elderly care homes. The Internet of Things infrastructure has been validated for Quantitative Gait Analysis showing an adequate accuracy in the demarcation of relevant gait events and in the estimation of stride interval variability. The latter, in combination with other characteristics that are commonly used to assess the state of frail elders and which come from anthropometric, biological, nutritional, functional, and mobility domains, allows us to perform a cross-sectional cohort study and a subsequent multiple logistic regression to evaluate their impact on cognitive functioning. The cohort study and the multivariate regression are performed using a sample of 81 frail elders from two nursing homes in Spain. The results obtained indicate that frail elders aged 90 years or older, with moderate dependence in daily functioning and with a stride interval gait variability greater than 6%, were most likely to suffer cognitive impairment, representing what is called cognitive frail.